2012
DOI: 10.1080/02773813.2012.698690
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Structural Changes During Liquefaction in Acidified Ethylene Glycol

Abstract: Beech (Fagus Sylvatica) milled-wood lignin was used as a model substrate in a study of lignin-catalyzed liquefaction in the presence of p-toluene sulfonic acid monohydrate (PTSA) or sulphuric acid as the catalysts. The structural changes that lignin undergoes during the treatment were studied by NMR spectroscopy, FTIR, size-exclusion chromatography, and high-performance liquid chromatography. For the sulphuric acid-catalyzed liquefaction, it was shown that the greater hydronium ion concentration in the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 25 publications
1
51
1
Order By: Relevance
“…Considering the lignin recovered in the solid residue, there was still approximately 50% and 55% unrecovered lignins and lignin derivatives in the ILs and EG solutions, respectively. The higher amounts of unrecovered lignin in EG solutions may be related to the formation of soluble lignin (or phenolics)eEG complex, which have been reported in previous studies on liquefaction of biomass [41,42].…”
Section: Lignin Recovery Processmentioning
confidence: 82%
See 1 more Smart Citation
“…Considering the lignin recovered in the solid residue, there was still approximately 50% and 55% unrecovered lignins and lignin derivatives in the ILs and EG solutions, respectively. The higher amounts of unrecovered lignin in EG solutions may be related to the formation of soluble lignin (or phenolics)eEG complex, which have been reported in previous studies on liquefaction of biomass [41,42].…”
Section: Lignin Recovery Processmentioning
confidence: 82%
“…However, lignin degradation was subsequently followed by the formation of soluble low molecular weight lignin derivatives. This may be attributed to the overall reduction of aliphatic hydroxyl groups [42]. Soda lignin also has the highest proportion of condensed phenolic groups, indicating that the lignin condensation reaction was more severe under the conditions used in pretreatment.…”
mentioning
confidence: 98%
“…Regarding the hydroxyl numbers obtained in this study (Table 1), which are quite low when compared to those reported for other polyols obtained from other lignocellulosic between the solubilized lignin with the hydroxyl groups present in the medium. Other concurrent degradation and condensation reactions between the lignin degradation fragments and 2-ethylhexanol may also occur contributing to the decrease of the OH number [25].…”
Section: Acid and Hydroxyl Numbermentioning
confidence: 99%
“…The liquefaction of biomass, such as lignocellulosic residues (residues containing cellulose and lignin), is a process that has been widely investigated, and is used in the depolymerization and solubilization of biomass at moderate temperatures (120 °C to 180 C) in polyhydric alcohols, which usually resorts to acid catalysts (Balat 2008;Jasiukaityte et al 2009;Jasiukaitytė-Grojzdek et al 2012;Kunaver et al 2012;Briones et al 2012;Hu and Li 2014;Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%